A case-control study of serum and tissue catalase among morphological variants of vitiligo - Nandhini Periasamy; V Ramesh; Monika Matlani (Wolters Kluwer Medknow Publications, 2023)
Background: Role of oxidative stress in the pathogenesis of vitiligo. Aim: Estimation of serum and tissue catalase levels in morphological variants of vitiligo. Settings and Design: A prospective case-control study was conducted in the outpatient department of Dermatology in Safdarjung hospital. Materials and Methods: We estimated levels of serum and tissue catalase in 30 vitiligo patients and 30 matched healthy controls. Statistical Analysis: The data analysis was done in Statistical Package for Social Sciences (SPSS) version 21.0. Normality of data was tested by Kolmogorov-Smirnov test. Results: Serum and tissue catalase was lower in vitiligo patients than controls. Serum catalase was lowest in vulgaris type, whereas in the acrofacial type had lowest tissue catalase levels. Conclusion: Vitiligo patients have a generalized oxidative stress functioning at a higher pace as seen with decreased serum and tissue CAT which can well be taken as a marker of active disease and they can be helped with topical pseudoCAT preparations.